2021
DOI: 10.1093/jpp/rgab086
|View full text |Cite
|
Sign up to set email alerts
|

Vanillic acid–Zn(II) complex: a novel complex with antihyperglycaemic and anti-oxidative activity

Abstract: Objectives Our aim was to synthesize, characterize and evaluate the antihyperglycaemic and anti-oxidative properties of a new Zn(II) complex of vanillic acid. Methods The complex was synthesized using ZnSO4.7H2O and vanillic acid as precursors. NMR and FTIR techniques were used to characterize the synthesized complex. The cytotoxicity of the complex was measured. The antihyperglycemic and anti-oxidative properties of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The metabolic profiles of cecum content showed that (R)-10-hydroxystearate, the substrate for the formation of oleic acid, and phenylacetylglutamine, which was related to the liver damage ( 56 ), were both downregulated by Goji and Goji-trained microbiota. Goji and Goji-trained microbiota significantly increase the content of the digalacturonate of pectin metabolic product and vanillic acid associated with antioxidant ( 57 ) and anti-inflammatory ( 58 ). In the hub network of metabolites, we found that Goji regulated some metabolites in tryptophan metabolism, and significantly increased the level of indole and indoleacetic acid that act as Aryl hydrocarbon receptor (AhR) ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic profiles of cecum content showed that (R)-10-hydroxystearate, the substrate for the formation of oleic acid, and phenylacetylglutamine, which was related to the liver damage ( 56 ), were both downregulated by Goji and Goji-trained microbiota. Goji and Goji-trained microbiota significantly increase the content of the digalacturonate of pectin metabolic product and vanillic acid associated with antioxidant ( 57 ) and anti-inflammatory ( 58 ). In the hub network of metabolites, we found that Goji regulated some metabolites in tryptophan metabolism, and significantly increased the level of indole and indoleacetic acid that act as Aryl hydrocarbon receptor (AhR) ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Eight weeks old Sprague Dawley rats were procured from the animal facility of the university. The study was conducted as reported previously (Oke et al, 2021) with slight modifications. The animals were fasted overnight.…”
Section: Methodsmentioning
confidence: 99%
“…method recently reported(Oke et al, 2021) was adopted for this assay with slight modification. In a 48-well plate, approximately equal portions (300 ± 10 mg) of the harvested muscle tissues were pre-incubated for 25 min in 900 μl of Krebs buffer that contained different concentrations(10, 20, 40, and 80 μM in total incubation volume) the tested samples or 50 mU insulin (NovoRapid® FlexPen®, Novo Nordisk Limited, West Sussex, UK) as the positive (2) Glucose uptake( % ) = Δ GC of test or control − ΔGC of blank control Δ GC of blank control × 100 control.…”
mentioning
confidence: 99%
“…Many beneficial biological effects of hydroxybenzoic acids, including GA, PCA, SA, and VA, on the treatment and prevention of cardiovascular and metabolic diseases have been documented [157,191]. Meanwhile, the health beneficial properties of phenolic acids can be influenced by various factors such as poor stability, restricted bioavailability, and absorption [9,15,179].…”
Section: Bioavailabilitymentioning
confidence: 99%